Analisis Kasus Penggelapan Dana Nasabah BNI Cabang Ambon dalam Perspektif Hukum Perbankan - Bagus Dwi Artha Wardhana; Bintang Ahmad Julian; Esky Mas Pratama; Rico Fransisko; Surya Ramao (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2025)
The case of embezzlement of customer funds at Bank Negara Indonesia (BNI) Ambon Branch has become a national concern because it involves large losses and indicates weaknesses in the bank's internal supervision system. This also has an impact on public confidence in banking activities in Indonesia. This research aims to analyze the aspects of banking law that were violated in this case, their impact on public trust, and preventive measures that can be taken by financial institutions. The research method used is literature study and legal analysis with a descriptive-qualitative approach. The research results show that this embezzlement involved a violation of the principles of good banking governance, and provides important lessons about the need for strict supervision of internal transactions. This article recommends reform of the banking security system and increased consumer protection as solutions.